Simulation model for maize crop growth based on acquisition and allocation processes for carbohydrate and nitrogen - Bonato, O.; Schulthess, F.; Baumgaertner, J.U. (Elsevier, 1999)
A population model for maize growth and development driven by temperature, solar radiation, soil water and soil nitrogen is presented. A time-varying distributed delay model is used to describe the dynamics of the attributes number, biomass and nitrogen belonging to leaf, root, stem, grain, rachys and husk populations. Photosynthate production as well as water and nitrogen acquisition was simulated with a demand-driven ratio-dependent functional response model. Carbohydrate, water and nitrogen supply-demand ratios were calculated to control the growth of different populations of plant. The metabolic pool model was used to allocate carbohydrates to plant subunits. The model was validated with published observations and field data from a 95- and a 120-day variety grown at the Research Station of the International Institute of Tropical Agriculture in Calavi, in the southern part of the Republic of Benin (West Africa). It was concluded to satisfactorily represent crop phenology and growth patterns. Moreover, the model permitted the assessment of drought stress, soil nitrogen, and planting density effects on maize growth and development.